2016
DOI: 10.1111/tgis.12199
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modelling for High‐rise Land Administration

Abstract: Current land administration systems mainly use 2D plans to define and secure ownership rights associated with properties in high-rise buildings. These 2D plans may not effectively communicate and manage the spatial complexity associated with multi-layered and stacked properties in such buildings; additionally, multiple pages of plans (representing sections of the building) are required to represent all ownership boundaries. In response, land administration organizations have been investigating a 3D digital app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 26 publications
0
81
0
6
Order By: Relevance
“…The AEC industry is fragmented and information intensive [38], and there exist various 3D data formats from different vendors that hinder information exchange in this area [39]. Even though there exist many open BIM standards, such as BIMXML [40] and COINS [41], IFC is the primary open data schema used for information exchange within AEC/FM domains [33], which is EXPRESS-based and developed by buildingSMART (formerly the International Alliance for Interoperability) [42].…”
Section: Industry Foundation Classes (Ifc)mentioning
confidence: 99%
“…The AEC industry is fragmented and information intensive [38], and there exist various 3D data formats from different vendors that hinder information exchange in this area [39]. Even though there exist many open BIM standards, such as BIMXML [40] and COINS [41], IFC is the primary open data schema used for information exchange within AEC/FM domains [33], which is EXPRESS-based and developed by buildingSMART (formerly the International Alliance for Interoperability) [42].…”
Section: Industry Foundation Classes (Ifc)mentioning
confidence: 99%
“…Several researches have studied how to use BIM for modelling 3D property rights. See, for example, EL-Mekawy [5] and Atazadeh et al [18]. Furthermore, Stoter et al [14] have demonstrated the possibility to extract legal volumes from a BIM.…”
Section: Methodology For 3d Registrationmentioning
confidence: 99%
“…These are known as Building Format Plans, and the spatial units defined by them as Building Format Units. This form of 3D spatial unit is the most common internationally, and it appears that all jurisdictions that recognize 3D subdivision use this form [11,[16][17][18].…”
Section: Topology In Cadastral Datamentioning
confidence: 99%
“…It should be noted that, in the future not all survey plans may originate from surveys, but quite a number of them might result from design; e.g., BIM/IFC (Building Information Modeling/Industry Foundation Classes) [18]. Additionally, here too the role of topology is of equal importance, and topology encoding from this source needs further investigations.…”
Section: Future Workmentioning
confidence: 99%